Perancangan Deteksi Wajah Dan Pengenalan Wajah Menggunakan Metode Viola Jones Dan Jaringan Syaraf Tiruan Menggunakan Raspberry Pi - Darwin Manurung; Feri Candra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Development of modern technology today has made industry carry out various innovations. One of them is digital image processing, such as biometrics for Face Recognition. Face recognition application can be implemented in various fields, for example Security Systems for doors access from a room. The research is conducted at Integrated Service Unit (UPT) of Universitas Riau which is the center for processing and maintaining from its system, data and networks. This study aims to implement face detection and face recognition systems in real-time by using Raspberry Pi. The research does not build the whole security system, just part. Testing is done by using simulation software. This study uses Viola Jones Method to detect face area. Back propagation of Artificial Neural Networks is used to perform face data training and predict facial pattern data. Research testings are carried out based on several factors such as light intensity, distance, and camera position. Results of this study showed that system succeeded to detect and recognize different faces in 0.5m, 00 of camera slop, 101-167 lx of light intencity with average of the highest accuracy is 86.6%. Keyword : Face Detection, Face Recognition, Artificial Neural Network.